How Inquiry Learning Model Affects Students’ Learning Results and Critical Thinking Skills in Covid-19 Pandemic? - SP, Efvinggo Fasya Jaya; Sholeh, Maimun; Hermanto, Febrika Yogie (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
The study aimed to determine 1) how the effect of the inquiry learning model on critical thinking skills, 2) how the effect of the inquiry learning model on learning results and critical thinking skills, and 3) how the inquiry learning model affects learning results and critical thinking skills with attention to the Covid-19 pandemic. This research was a quantitative study with a survey approach. The data collection technique was carried out by observation and questionnaires with the 71 students of XII Grade in Yogyakarta 4 Senior High School. The results of the data analysis indicated that 1) the inquiry learning model had a significant effect on learning results with a level of effect of 73.0%, 2) the inquiry learning model had a significant effect on the critical thinking skills of 69.1%, 3) the inquiry learning model had a significant effect on learning results and critical thinking skills with p-value of 0.000 than 0.05. These results indicated that the inquiry learning model in the Covid-19 Pandemic era could improve the students’ learning results and critical thinking skills.